Clays and Clay Minerals, Vol. 54, No. 2, 165-175, 2006. - Perrier, Nicolas; Gilkes, Robert J.; Colin, Fabrice (The Clay Minerals Society, 2006)
Evidence for fire affecting the solubility of metals in Fe oxide-rich Oxisols of the Koniambo Massif of New Caledonia is presented. Acid-dissolution studies showed that Ni, Al and Cr are substituted for Fe in the structure of the Fe oxides. Thermal dehydroxylation of goethite under oxidizing conditions led to the formation of hematite and to the migration of some of these metals towards the surface of hematite crystals as indicated by their enhanced release during the early stage of dissolution. Dehydroxylation of goethite under reducing conditions led to the formation of hematite and maghemite. Nickel and Al were released preferentially during the early stages of dissolution whereas Cr was not released preferentially and may be uniformly incorporated within maghemite and hematite crystals. These results have significance to the mineral-processing industry, to geochemical exploration and to the availability of these metals to plants growing on burnt soils.
Heating Fe Oxide-Rich Soils Increases the Dissolution Rate Of Metals
gsccm-54-2-03-per.pdf 462KB PDF/A Document
Keywords: Periodicals; Geology; Goethite; Maghemite; Hematite; Dehydroxylation Acid Dissolution; Lateritic Ore; New Caledonia